The 3D Tune-In Toolkit - 3D audio spatialiser, hearing loss and hearing aid simulations - Cuevas-Rodriguez,M; Gonzalez-Toledo,D; La,Rubia-Cuestas ED; Garre,C; Molina-Tanco,L; Reyes-Lecuona,A; Poirier-Quinot,D; Picinali,L (2018)
The 3DTI Toolkit is a standard C++ library for audio spatialisation and simulation using loudspeakers or headphones developed within the 3D Tune-In (3DTI) project (http://www.3d-tune-in.eu), which aims at using 3D sound and simulating hearing loss and hearing aids within virtual environments and games. The Toolkit allows the design and rendering of highly realistic and immersive 3D audio, and the simulation of virtual hearing aid devices and of different typologies of hearing loss. The library includes a real-time 3D binaural audio renderer offering full 3D spatialization based on efficient Head Related Transfer Function (HRTF) convolution, including smooth interpolation among impulse responses, customization of listener head radius and specific simulation of far-distance and near-field effects. In addition, spatial reverberation is simulated in real time using a uniformly partitioned convolution with Binaural Room Impulse Responses (BRIRs) employing a virtual Ambisonic approach. The 3D Tune-In Toolkit includes also a loudspeaker-based spatialiser implemented using Ambisonic encoding/decoding. This poster presents a brief overview of the main features of the Toolkit, which is released open-source under GPL v3 license (the code is available in GitHub https://github.com/3DTune-In/3dti-AudioToolkit).